Avicenna’s Ontological Analysis of Aristotle`s Ousia - E Taheri Sarteshnizi (Metaphysics, 2013)
Avicenna may be regarded as the first Muslim philosopher who has perceived a deep connection between Aristotelian concept of ousia and being and, analyzing the concept ontologically, he tried to correct the failures of Aristotle’s thought in this field. In this way, the ambiguity of the subject-matter of first philosophy has been omitted and the capability of Aristotle’s philosophical teachings is used for establishing a religious philosophy. As is explained, in spite of considerable changes made in contemporary studies on Aristotle`s philosophy, Avicenna can be regarded as a perfect authority in this field.